2021
DOI: 10.21837/pm.v19i15.921
|View full text |Cite
|
Sign up to set email alerts
|

Green City Initiatives: Human-Nature Interaction

Abstract: Interaction with Nature [IN] refers to the urge or preference to be close to the natural environment, attentiveness and knowledge of the natural environment, and health associated attributes in relation to surroundings. Issue: Since the vision of green city was introduced, Melaka has made great strides toward building a sustainable, green city. With the ongoing development towards reduction of carbon intensity 2020, IN of Melaka public needs to be evaluated to determine the human-nature connection with respect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Forming a green city must adjust the service ecosystem that is connected to nature. Drastic global climate change has invited many cities to compete in issuing quantitative parameters that classify and track environmental friendliness-social welfare-economic consistency over time ( Abu Bakar et al, 2021). The outcomes of these three trends, make it a valuable tool in the "quality of green cities" index.…”
Section: Green Citymentioning
confidence: 99%
“…Forming a green city must adjust the service ecosystem that is connected to nature. Drastic global climate change has invited many cities to compete in issuing quantitative parameters that classify and track environmental friendliness-social welfare-economic consistency over time ( Abu Bakar et al, 2021). The outcomes of these three trends, make it a valuable tool in the "quality of green cities" index.…”
Section: Green Citymentioning
confidence: 99%
“…Interaction with Nature [IN] is the second dimension of HIE that focuses on emotional empathy, closeness, familiarity, and both voluntary and involuntary interactions with the natural world. Among the numerous traits of IN are the desire to be closer to the natural environment, understanding of and empathy toward the natural environment, and health-related implications associated with one's natural surroundings (Abu Bakar et al, 2021;Abu Bakar et al, 2020c). Bakar et al, 2018;Abu Bakar et al, 2017a;Abu Bakar et al, 2017b), can be observed in Table 1.…”
Section: Interaction With Naturementioning
confidence: 99%
“…In this regard, IN enriches focus as well as being entirely present in the moment. This state of mind corresponds to the essence of transcendence since both require heightened awareness of the present moment and a sensation of pushing beyond regular limitations (AbuBakar et al, 2021;Abu Bakar et al, 2020c). Experiencing transcendence through IN cultivates a sense of tranquillity, profound introspection, and interconnectedness with the environment.In light of this knowledge, the following questions were investigated in the paper: Does the fulfilment of human needs elevate IN?…”
mentioning
confidence: 99%